3.2k views
18 votes
Solve the following system of equations using the substitution method

y - 3x = 12

y = - 3​

2 Answers

10 votes

Answer:

x = -5

y = -3

Explanation:

Two equations

Solve using substitutition

y = -3

y - 3x = 12

_____________________

Since the first equation has y alone, we can plug it into the second equation for y.

(-3) - 3x = 12

-3 - 3x = 12

Add 3 to both sides :

-3x = 15

Divide -3 from both sides to get x alone :

x = -5

Now that we have x, plug it into x in the second equation :

y - 3(-5) = 12

y + 15 = 12

Solve for y :

Subtract 15 from both sides :

y = -3

User Jujule
by
4.9k points
3 votes

Answer:

x = 5

y = -3

as an ordered pair: (5,-3)

Explanation:

if y = -3, then replace y in the first equation with -3.

-3 - 3x = 12

move -3 over to the other side by adding 3 to both sides.

3x = 15

x = 5

y = -3

User Paaji
by
4.9k points